Students’ mathematical justification abilities in analyzing ChatGPT’s answers - Sutrisno AB, Joko; Pratama, Elvandri Yogi; Putra R, Andika; Nasution, Syaiful Hamzah; Lestyanto, Latifah Mustofa (IKIP Siliwangi and I-MES, 2025)
This study investigates students' mathematical justification abilities in analyzing answers obtained from one of the Artificial Intelligence (AI) based services, namely ChatGPT. The subjects of this descriptive qualitative study are 13 fourth-semester students of STKIP-PGRI Bandar Lampung. They were asked to utilize ChatGPT to solve two linear equation system questions adopted from Indonesian university entrance tests in 2019. The students were then requested to analyze and justify the responses generated by ChatGPT. The justifications from students were then analyzed to see their abilities and determine whether the answers from ChatGPT were correct. As many as 61.54% of the respondents could understand the instructions of the two questions and provide reviews for the answers generated by ChatGPT. 38.46% of the respondents did not understand the questions' instructions. The results showed that students may have lacked the necessary ability to analyze the AI-generated answers in depth and explain them in detail. This may be due to weak mastery of the basic concepts of the material and a lack of accuracy. The findings call for paying more attention to students' mathematical justification abilities in the current AI-assisted era.